1996
DOI: 10.1128/jvi.70.8.5495-5502.1996
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of mouse adenovirus type 1 infection on cell surface expression of major histocompatibility complex class I antigens

Abstract: It has been proposed that adenoviruses establish and maintain persistent infections by reducing the class I major histocompatibility complex-associated presentation of viral antigens to cytotoxic T lymphocytes, leading to ineffective cell-mediated immunity and impaired clearance of infected cells (W. S. M. Wold and L. R. Gooding, Virology 184:1-8, 1991). Early region 3 of human adenovirus types 2 and 5 encodes a 19-kDa glycoprotein that associates with the class I major histocompatibility complex (MHC) antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It will be interesting to determine what factors allow the virus to persist in the host and what aspects of the immune system are important in maintaining this delicate balance. Previous studies have shown that MAV-1 does not decrease MHC-I surface expression of cultured infected cells (36). Down-regulation of MHC-I has been proposed as a possible mechanism for evading the immune system response by human adenoviruses.…”
Section: Discussionmentioning
confidence: 97%
“…It will be interesting to determine what factors allow the virus to persist in the host and what aspects of the immune system are important in maintaining this delicate balance. Previous studies have shown that MAV-1 does not decrease MHC-I surface expression of cultured infected cells (36). Down-regulation of MHC-I has been proposed as a possible mechanism for evading the immune system response by human adenoviruses.…”
Section: Discussionmentioning
confidence: 97%
“…The balance of NK cell activation vs. inhibition can be shifted toward activation of cytotoxicity when NK cells detect target cells expressing reduced levels of MHC class I (reviewed in Biron and Sen, 2007). A previous finding suggests that NK cell recognition of "low MHC class I" cells may not be important for control of MAV-1 infection: MAV-1 infection does not decrease MHC class I expression (Kring and Spindler, 1996). This may reduce the need for NK cell-mediated cytolysis of cells lacking MHC class I. NK cells in mice deficient for MHC class I are defective in target killing (Yokoyama and Kim, 2006).…”
Section: Depletions Of Nk Cells By Anti-asialogm1 and Pk136 Antibody mentioning
confidence: 97%
“…Many viruses have mechanisms to downregulate MHC class I, thus protecting them from CD8 + T cell killing, but making them potentially susceptible to NK cell killing. However, MAV-1 does not downregulate MHC class I during infection (Kring and Spindler, 1996). This suggests that the cytotoxic function of NK cells might not be necessary for control of MAV-1 infection.…”
Section: Introductionmentioning
confidence: 97%
“…For example, one of the first viral immune evasion strategies identified for any virus is downregulation of class I major histocompatibility complex (MHC) antigens on the surface of infected cells by HAdV‐2 . This function of HAdV E3 gp19K is not mimicked by MAdV‐1 infection . The MAdV‐1 E3 proteins do not have sequence similarity to other known proteins.…”
Section: Mouse Adenovirus Typementioning
confidence: 99%
“…MAdV‐1 also causes myocarditis that is accompanied by myocyte and endothelial necrosis when inoculated intraperitoneally or intranasally . Many mouse primary cell types, cell strains, and established cell lines can support MAdV‐1 replication in vitro , including fibroblasts (3T6, 3T12 and L929) , endothelial cells (MBMEC) , preadipocyte cells (3T3‐L1) , epithelial cells (LA‐4, MLE‐12 and MLE‐15; J.B. Weinberg, unpublished), cardiac myocytes macrophages/monocytes , and tumor cells such as lung adenoma (LA‐4), renal adenocarcinoma (RAG) , and rectal carcinoma (CMT‐93) cells .…”
Section: Madv‐1 Pathogenesis—tropism Adaptive Immune Responsesmentioning
confidence: 99%